Casey at the bat - Thayer, Ernest Lawrence. 1863-1940.; Moser, Barry (Boston : D.R. Godine, 1988)
A narrative poem about a celebrated baseball player who strikes out at the crucial moment of a game.
Keywords: Baseball -- Poetry; Baseball -- Poetry; American poetry